Hamiltonety and automorphisms group of graph preserved by substitution - Montenegro, Eduardo (CUBO, A Mathematical Journal, 1995)
The substitution is a graph operation. This operation consists in replacing a vertex by a graph. The aim of this work is to analize the preservation of certain properties in the substitution of a graph. Specifically, these properties are: (i) hamiltonety and (ii) group of automorphisms of a given graph G.